2011
DOI: 10.5367/te.2011.0027
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Performance of Australian Hotels: A DEA Double Bootstrap Approach

Abstract: This study uses the data envelopment analysis (DEA) double bootstrap approach to assess the technical efficiency standing of Australian hotels. Two inputs and six outputs were used in the analyses for the period 2004-2007. The empirical results indicate that the DEA bootstrap approach corrects for the bias inherent in traditional DEA models. The results show that the average technical efficiency of Australian hotels has improved gradually from 76.17% in 2004 to reach its highest level of 80.84% in 2007. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 35 publications
3
88
1
1
Order By: Relevance
“…These include, the age (number of years a hotel has been in firm) and 'star rating' of each hotel. These variables have been used in previous studies in the literature (Good et al, 1993;Ray and Mukherjee, 1994;Barros and Dieke, 2008;Assaf and Agbola, 2009). Star rating is a reflection on quality (Assaf and Knežević, 2011), and the age of a hotel is a reflection on the experience that a particular hotel develops over time (Assaf and Knežević, 2011).…”
Section: Control Variablesmentioning
confidence: 98%
“…These include, the age (number of years a hotel has been in firm) and 'star rating' of each hotel. These variables have been used in previous studies in the literature (Good et al, 1993;Ray and Mukherjee, 1994;Barros and Dieke, 2008;Assaf and Agbola, 2009). Star rating is a reflection on quality (Assaf and Knežević, 2011), and the age of a hotel is a reflection on the experience that a particular hotel develops over time (Assaf and Knežević, 2011).…”
Section: Control Variablesmentioning
confidence: 98%
“…Previous empirical literature suggests that hotel classification (based on the star rating) play an important role in explaining the performance and efficiency of hotels (Ray and Phillips, 2005;Assaf and Agbola, 2011). We use a similar binary variable, CLASS, that assumes 1 if the firm hold five-star hotels and 0 otherwise.…”
Section: Independent Firm-level Variablesmentioning
confidence: 99%
“…These variables are in line with previous studies in the area (Good et al, 1993;Ray and Mukherjee, 1994;Barros and Dieke, 2008). Assaf and Agbola (2009) have also recently tested the impact of the same variables on the effi ciency of Australian hotels, and concluded that they all lead to effi ciency improvement. However, as Slovenia operates in a much smaller context and in different environmental characteristics, it would be interesting to check if these fi ndings remain the same.…”
Section: Data Descriptionmentioning
confidence: 99%